2013
DOI: 10.1016/j.ejvs.2013.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Imaging Features and Classification of Isolated Dissection of the Superior Mesenteric Artery

Abstract: The new classification is useful for describing the imaging features of isolated dissection of the SMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…In addition, our study revealed that SMAD usually developed in middle-aged men with a history of smoking and that SMAT usually developed in older patients with a history of atrial fibrillation and hypertension. However, it should be noted that enhanced CT is needed to make a diagnosis of AMI [8][9][10][11]24,25].…”
Section: Patient Characteristics and Ct Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our study revealed that SMAD usually developed in middle-aged men with a history of smoking and that SMAT usually developed in older patients with a history of atrial fibrillation and hypertension. However, it should be noted that enhanced CT is needed to make a diagnosis of AMI [8][9][10][11]24,25].…”
Section: Patient Characteristics and Ct Findingsmentioning
confidence: 99%
“…There are several choices for assessment of the intestinal condition in such patients such as invasive exploratory laparotomy for laparoscopic vision and exploratory surgery for direct vision [6,7]. On the other hand, it has been reported that the use of computed tomography (CT) with or without contrast medium enhancement has the potential to evaluate the presence or absence of intestinal ischemia and necrosis less invasively than exploratory surgery [8][9][10][11]. There have been several CT findings previously suggested as the predictive finding of intestinal ischemia and necrosis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the absence of the ileocolic branch might be caused by developmental variation or occlusion owing to extension of the dissection. Although the ileocolic artery was a constant branch of the SMA, 1 the absence of the ileocolic branch was observed in 25% cases. 2 According to our classification scheme, 3 types C and D were defined with the dissections localized at the curved part of the SMA and extended distally without or with involved ileocolic or distal ileal branches.…”
mentioning
confidence: 94%
“…We read with interest the article by Luan and Li classifying isolated dissections of the superior mesenteric artery (SMA). 1 Having recently encountered a patient with a "Type C" dissection, we wish to highlight the decision process we undertook as a result of two anatomical variations that did not fall into their or others classifications. 2 The first was the absence of an ileocolic branch of the SMA, which manifested as multiple small branches (jejunal/ ileal) arising from a single origin.…”
mentioning
confidence: 99%